Magnetic resonance imaging reveals microemboli-mediated pathological changes in brain microstructure in diabetic rats: relevance to vascular cognitive impairment/dementia. Issue 21 (10th November 2022) - Chandran, Raghavendar; He, Lianying; Nie, Xingju; Voltin, Joshua; Jamil, Sarah; Doueiry, Caren; Falangola, Maria Fatima; Ergul, Adviye; Li, Weiguo
Abstract: Diabetes doubles the risk of vascular cognitive impairment, but the underlying reasons remain unclear. In the present study, we determined the temporal and spatial changes in the brain structure after microemboli (ME) injection using diffusion MRI (dMRI). Control and diabetic rats received cholesterol crystal ME (40–70 µm) injections. Cognitive tests were followed up to 16 weeks, while dMRI scans were performed at baseline and 12 weeks post-ME. The novel object recognition test had a lower d2 recognition index along with a decrease in spontaneous alternations in the Y maze test in diabetic rats with ME. dMRI showed that ME injection caused infarction in two diabetic animals ( n =5) but none in controls ( n =6). In diabetes, radial diffusivity (DR) was increased while fractional anisotropy (FA) was decreased in the cortex, indicating loss of tissue integrity and edema. In the dorsal hippocampus, mean diffusivity (MD), axial diffusivity (DA), and DR were significantly increased, indicating loss of axons and myelin damage. Histological analyses confirmed more tissue damage and microglial activation in diabetic rats with ME. These results suggest that ME injury and associated cerebrovascular dysfunction are greater in diabetes, which may cause cognitive deficits. Strategies to improve vascular function can be a preventive and therapeutic approach for vascular cognitive impairment.